The characteristics and prescription patterns of Chinese herbal medicine in clinical practice for the treatment of anemia - Wei-Di Chen; Hung-Sen Huang; Yuan-Chih Su; Shen-Chieh Chou; Wen-Chao Ho; Ming-Ching Kao; Hung-Jen Lin; Sheng-Teng Huang (Elsevier, 2018)
Objective: Chinese herbal medicine (CHM) is frequently applied to patients to improve the symptoms and signs associated with anemia. The aim of this study is to use the claims data from the National Health Insurance Research Database (NHIRD) in Taiwan to analyze CHM prescription patterns and to identify the frequency and combinations of CHM commonly used to treat anemia. Materials and methods: A total of 41,028 patients were diagnosed with anemia in Taiwan within the defined study period. After randomly equal matching for age and sex, data from 7682 patients characterized as CHM users and non-users were analyzed. Network analyses of the 30 most frequently applied herbs and formulas were used to indicate CHM combinations in patients with anemia. Results: Those patients with anemia who were older, office workers, and lived in central areas of Taiwan had higher tendencies toward CHM usage. Based on considerations of comorbidities, anemia patients associated with chronic kidney diseases, diabetes mellitus, and hypertensive diseases preferred Western medical management and demonstrated a lesser likelihood of combining treatment with CHM; by contrast, those with coronary artery disease demonstrated a higher tendency for CHM use. Notably, Astragalus membranaceus (AM) and Gui-Pi-Tang (GPT) were the most commonly prescribed CHM single herb and formula, respectively. The core prescription pattern consisted of AM, Salvia miltiorrhiza (SM), Angelica sinensis (AS), GPT, and Si-Wu-Tang (SWT), as indicated by the associations and frequency of CHM utilization by traditional Chinese medicine (TCM) physicians. Conclusion: This study demonstrates that CHM may be applied as an integral element of treatment for patients with anemia. It also provides insight regarding individual therapy and common clinical practices of TCM physicians in the treatment of anemia. Further research is required to explore potential interactions and possible mechanisms at play with CHM management of anemia. Keywords: Chinese herb medicine, Anemia, Cohort study, Prescription pattern